Eksistensi Budaya Lewak Tapo di Tengah Arus Modernisasi: Studi Kasus di Desa Sukutokan, Kecamatan Klubagolit, Kabupaten Flores Timur, Provinsi Nusa Tenggara Timur - Masudin Shaleh; Sari Mellina Tobing; Rizki Agung Novariyanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Culture is manifested in several forms such as behavior, myths, beliefs and many other forms of culture. The birth of culture is caused by human desire to meet the needs of life. These desires form a tradition that is passed down from generation to generation. Meanwhile, culture can be interpreted as a view in looking at good or bad human experience in interacting and influencing the way of thinking. In the cultural life of a community group, it will not be separated from the flow of modernization which brings changes in all aspects of life. This is one of the indications and the need for confirmation in an effort to maintain the existence of local culture. In this study the authors conducted research related to the existence of the lewak tapo ritual in Sukutokan Village, Kelubagolit District. The data sources used in this study are primary data sources and literature obtained by interview techniques. In this study the authors analyzed the data with descriptive qualitative techniques which aim to describe phenomena in the field. The findings in this study illustrate that the lewak tapo ritual itself contains social meanings and beliefs. Social meaning is realized through social values that are built such as the values of togetherness, mutual cooperation, justice and solidarity. Meanwhile, the meaning of belief is realized through communication relations that are built between families who are still alive and family members who have died unnaturally. The message contained in this ritual is awareness not to repeat the same mistake because the purpose of this ritual is to find the cause of someone's death in an unnatural way. Given that this ritual is a sacred ritual, the existence of this ritual has indirectly been treated because of awareness of unnatural deaths.